2019
DOI: 10.1080/17512549.2019.1575770
|View full text |Cite
|
Sign up to set email alerts
|

Household factors and electrical peak demand: a review for further assessment

Abstract: At least one-third of the total electricity generation of a country is consumed by the residential sector, which is one of the most unpredictable consumer groups with respect to electricity usage and thus risks network security by producing peaks in demand. Consequently, a growing body of literature has paid particular attention to this sector and explored the household factors responsible for residential electricity consumption. However, comprehensive studies that explicitly considered all these factors in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 164 publications
(270 reference statements)
0
12
0
Order By: Relevance
“…Effective demand-side management strategy design for the residential sector depends on proper identification of factors that are responsible for driving electricity demand at houses. A large and growing body of literature has investigated different household factors such as building characteristics, socio-demographic characteristics and found relationship in driving residential electricity demand [115][116][117][118][119][120][121]. For example, Brounen et al (2012) found that electricity consumption at houses varies predominantly due to family composition and income of the household [117].…”
Section: Factors Responsible For Residential Demandmentioning
confidence: 99%
See 3 more Smart Citations
“…Effective demand-side management strategy design for the residential sector depends on proper identification of factors that are responsible for driving electricity demand at houses. A large and growing body of literature has investigated different household factors such as building characteristics, socio-demographic characteristics and found relationship in driving residential electricity demand [115][116][117][118][119][120][121]. For example, Brounen et al (2012) found that electricity consumption at houses varies predominantly due to family composition and income of the household [117].…”
Section: Factors Responsible For Residential Demandmentioning
confidence: 99%
“…In India, Filippini and Pachauri (2004) found that area of the house and demographic characteristics such as 'age of the head of the house' have large impact on electricity consumption in urban area [119]. A recent review study considered most of these household factors that contribute to electricity demand including peak demand at houses, in which the author categorized the factors as 'climate and location of the dwelling', 'physical characteristics of the dwelling', 'household activities and services', 'economic capability', 'sociodemographic characteristics', 'cost of energy', and 'potential drivers of future residential consumption' [115].…”
Section: Factors Responsible For Residential Demandmentioning
confidence: 99%
See 2 more Smart Citations
“…Customers who favor larger dwellings or older households tend to have higher peak demand. 7 There has also been evidence that psychological factors such as customer attitudes, habits, and personal motivations all influence the variation in electricity demand 8,9 ; in particular, it has been noted that conservative customers tend to use less electricity, but in a more consistent manner, thus reducing quantity risk. 8,9 In this vein, Torriti 10 modeled quantity risk in five European countries and showed that increasing peak electricity use may increase quantity risk.…”
Section: Introductionmentioning
confidence: 99%